PENGARUH FRAUD INDICATORS TERHADAP FRAUDULENT FINANCIAL STATEMENT: STUDI EMPIRIS PADA PERUSAHAAN YANG LISTED DI BURSA EFEK INDONESIA (BEI) TAHUN 2008-2013 - Ismah Hanifa, Septia; Laksito, Herry (Diponegoro Journal of Accounting, 2015)
This study aimed to examine the effect of fraud indicators against the detection of fraudulent financial statement on non-financial company listed on the Indonesian Stock Exchange (BEI) in the period 2008–2013. Variables used in this research are financial stability, external pressures, financial target, debt, liquidity, performance, the effectiveness of supervision, the quality of the external auditor and the change of directors.The research was conducted by quantitative methods using secondary data. The secondary data came from a list of cases Otorisasi Jasa Keuangan (OJK) and non-financial companies annual report listed on the Indonesian Stock Exchange. This research population is company listed on the Indonesian Stock Exchange period 2008-2013, and then the samples were taken by purposive sampling with criteria non-financial company and have the required data in this study. The research uses logistic regression statistical tools because the dependent variable was dummy variable (non metric), while the independent variable was metric and non metric variable.The results showed that the fraud indicators of financial stability has a positive influence on fraudulent financial statement, while the fraud indicators (financial target and performance) have a negatively affect the fraudulent financial statement.